FOOTWEAR SECTOR IN INDIA: A ROLE OF ADVANCED TECHNOLOGIES - Kumar, Neeraj; Gupta, Varun (International Journal of Research -GRANTHAALAYAH, 2016)
Footwear sector is a very significant segment of Leather and NonLeather products in India. The size of Indian Domestic Footwear Industry is estimated to be worth 1919 million pairs where leather and non-leather Footwear per capita consumption is estimated to be approx. 1.61 pairs. The major component of footwear sector is a design, product development, clicking, closing, component, lasting & finishing. Advanced technologies in the area of shoe design systems, automation, cost savings and productivity improvements as well as enabling new developments in footwear sector in India. Although today footwear is produced using many similar methods to those employed all those years ago, obvious technological innovations in machinery, raw materials, production and testing techniques have changed what was to all intents and purposes a cottage industry into a multi-billion dollar sector. At the same time, recent years have seen a distinct shift in factory location away from the traditional industrial heartlands of Europe and North America to the new lands of opportunity, primarily in Asia. The purpose of this paper is to review the areas where advanced technologies can significantly affect the way of footwear sector is practiced. Strategies for implementation of the necessary changes in practice are also discussed.